Novel algorithm for designing reflect-array antennas based on analytical methods - Nasrollahi, H.; Fallah, M.; Nazeri, Amir H.; Abdolali, A. (International journal of electronics and communications, 2018)
This paper presents a comprehensive and accurate algorithm based on circuit model to design reflect-array antennas (RAAs). The proposed algorithm can extract geometry of RAA structure corresponding to radiation parameters without employing any approximation or optimization intervention into the algorithm. Simulation results for some comprehensive examples, verify the validity of the proposed algorithm. This method is simple, fast, accurate, and can be expanded to all species of RAAs with arbitrary geometries. One of the main problems confronted in RAAs is low bandwidth characteristics. To attain wide bandwidth, we exploited the proposed algorithm with combination of multi-layer design of RAAs and subwavelength element. Convergence is observed between simulation and fabrication results, asserting good accuracy in method. In 10–15 GHz band, the maximum gain and -1dB bandwidth of two-layer antenna is 31.4 dB and 18.5%, respectively.